Effects of olive leaf extract and vitamin E supplementation in quail diet on some blood parameters and egg yolk fatty acids composition - Ozdemir, Ayhan; Azman, Mehmet Ali (Ankara Univ Press, 2016)
This experiment was performed to investigate the effect of dietary supplementation with olive leaf extract on some blood parameters and egg yolk fatty acid composition of laying quails. A total of 192 Japanese quail (Coturnix coturnix japonica) 60 d old were allocated to 4 treatment groups with 4 replicates each containing 12 birds. Birds housed in cages and water and feed were given ad libitum during the total period of experiment. The quails received a basal diet (maize and soyabean meal based; 19.1% CP, 2.940 kcal/kg ME, 3.0% Ca and 0.39% P av) that was formulated including vitamins and minerals. Diets were prepared as control (basal diet, group Control), basal diet plus 200 mg a-tocopherol acetat/kg (group E), and basal diet plus 80 or 120 ppm Oleuropein (OLE) (group OLE-80 and OLE-120). At the end of the experiment, egg yolks samples were analysed; cholesterol levels of groups fed diets with OLE-80 and OLE-120 were significantly higher than the groups fed control diet (p<0.01); vitamin A levels of groups fed diets with vit. E were significantly lower than the groups fed control diet and containing OLE-80 (p<0.05) and vitamin E levels were significantly higher than the other groups (p<0.001). The supplementation of olive leaf extract were influenced to fatty acid composition of egg yolk lipids. The concentration of oleic and linoleic acids in egg yolks were higher in OLE-80 than the others groups (p<0.05). The concentration of PUFA, n-6 fatty acids and n-6/n-3 fatty acids ratio were the highest in OLE-80 groups than the other groups. These results showed that the supplementation of 80 ppm OLE in quail diets was conducted to increase of oleic, linoleic and n-6 fatty acids, and n-6/n-3 fatty acids ratio in egg yolks.
Bıldırcın rasyonlarına zeytin yaprağı özütü ve E vitamini katılmasının bazı kan parametreleri ve yumurta sarısı yağ asitleri kompozisyonu üzerine etkileri
Keywords: Blood parameters; egg yolk fatty acids; olive leaf extract; quail; vitamin E